2010
DOI: 10.1002/pmic.200900650
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physiological, ultrastructural and proteomic analyses reveal sexual differences in the responses of Populus cathayana under drought stress

Abstract: Drought is a major abiotic stress, limiting the survival and growth of young plants. However, little is known about sex-dependent responses to drought at the proteome level. In this study, we carried out investigations on comparative proteomics, combined with physiological and organelle structure analyses, in males and females of Populus cathayana Rehd. Three-month-old poplar cuttings were treated at 30% of field capacity and at 100% field capacity as a control in a greenhouse for 40 days. Drought greatly inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 72 publications
7
83
0
Order By: Relevance
“…Vacuolized chloroplasts with thylakoidal membrane distortions in mesophyll cells of sensitive apple (Malus hupehensis) leaves were described by Wang et al (2012a,b). Drought stressinduced destruction of chloroplast structures was also found in female poplar (Zhang et al, 2010). In our experiments, rapid or severe loss of cellular integrity was a hallmark of drought sensitivity.…”
Section: Discussionmentioning
confidence: 64%
“…Vacuolized chloroplasts with thylakoidal membrane distortions in mesophyll cells of sensitive apple (Malus hupehensis) leaves were described by Wang et al (2012a,b). Drought stressinduced destruction of chloroplast structures was also found in female poplar (Zhang et al, 2010). In our experiments, rapid or severe loss of cellular integrity was a hallmark of drought sensitivity.…”
Section: Discussionmentioning
confidence: 64%
“…As the different reproduction costs, males and females have evolved different adaptive strategies to environmental stresses (Dawson and Bliss, 1989;Dawson and Ehleringer, 1993). Our previous studies have shown that there are different tolerance and sensitivity in male and female poplars to nitrogen deposition, photoperiod, heavy metals, sanity, chilling and rust disease (Zhao et al, 2009(Zhao et al, , 2011Chen et al, 2010a,b;Zhang et al, 2010aZhang et al, , 2011. In these studies, we found a common phenomenon that male poplars showed higher antioxidant enzyme activities than females under the above stresses.…”
Section: Introductionmentioning
confidence: 74%
“…These results suggest that sexually different responses in antioxidants are distinct. A previous proteome study also discovered that APX and peroxidase proteins exhibit a higher abundance in drought-stressed males than in drought-stressed females (Zhang et al, 2010a).…”
Section: Males Showed a Better Protective Mechanism Than Females Undementioning
confidence: 87%
See 1 more Smart Citation
“…In addition, recent literatures showed that both stress adaptive capacity and resource availability are two important factors affecting secondary sexual dimorphism. In general, females are more sensitive and poorer adaptive to stress conditions than males, which could be deduced from changes in physiology, biochemistry, transcriptome and proteome levels when plants are exposed to stress conditions (Dudley and Galen 2007;Chen et al 2010Chen et al , 2011Zhang et al 2010;Jiang et al 2012). On the other hand, resource availability may also influence distribution of dioecious plants.…”
Section: Introductionmentioning
confidence: 99%